TEKNIK PEMERIKSAAN KEABSAHAN DATA DALAM RISET ILMIAH - M. Husnullail; Risnita; M. Syahran Jailani; Asbui (LPPM Universitas Cipta Mandiri, 2024)
Collecting data and then processing it is not an easy task. Because if you obtain incorrect or inappropriate data, the results of the processing will also be incorrect or inappropriate. The validity of data is an important factor in scientific research. This paper is written to understand the technique of examining the validity of data in scientific research. The approach in this paper uses literature study with data collection technique using documentation, such as books and scientific articles related to the theme of this paper. Data analysis technique is done through data reduction, data presentation, and drawing conclusions. The results of this study can be summarized that in the technique of examining the validity of data, there are four criteria used in data validity testing, namely: credibility, transferability, dependability, and confirmability. And there are four types of triangulation as techniques for examining the validity of data, namely: source usage, method, inter-researcher, and theory.